2005
DOI: 10.1037/0735-7044.119.1.280
|View full text |Cite
|
Sign up to set email alerts
|

Ferret Odor as a Processive Stress Model in Rats: Neurochemical, Behavioral, and Endocrine Evidence.

Abstract: Predator odors have been shown to elicit stress responses in rats. The present studies assessed the use of domestic ferret odor as a processive stress model. Plasma corticosterone and adrenocorticotropin hormone levels were higher after 30 min of exposure to ferret odor (fur/skin) but not control odors, ferret feces, urine, or anal gland secretions. Behavioral differences were also found between ferret and the control odors as tested in a defensive withdrawal paradigm. In addition, c-fos messenger RNA expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

18
91
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 118 publications
(109 citation statements)
references
References 53 publications
18
91
0
Order By: Relevance
“…Consistent with previous studies using cat odor as a stimulus (Dielenberg et al, 2001;McGregor et al, 2004) we found that 10 min of ferret exposure resulted in a robust increase in the number of Fos-positive cells within the MeA. Similarly, c-fos mRNA was increased in the MeA of rats immediately after a 30 min exposure to ferret odor (Masini et al, 2005). The MeA, which lies medial to the CeA, showed the largest increase in c-fos expression within the amygdala and is of interest because earlier studies associated it with fear and defensive responses (Kemble et al, 1984).…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Consistent with previous studies using cat odor as a stimulus (Dielenberg et al, 2001;McGregor et al, 2004) we found that 10 min of ferret exposure resulted in a robust increase in the number of Fos-positive cells within the MeA. Similarly, c-fos mRNA was increased in the MeA of rats immediately after a 30 min exposure to ferret odor (Masini et al, 2005). The MeA, which lies medial to the CeA, showed the largest increase in c-fos expression within the amygdala and is of interest because earlier studies associated it with fear and defensive responses (Kemble et al, 1984).…”
Section: Discussionsupporting
confidence: 91%
“…Similarly, exposure to the odor of a ferret has been reported to increase rat corticosterone levels (Masini et al, 2005). In the present study corticosterone concentrations peaked 15 min after cessation of 10 min of ferret exposure and returned to baseline by 120 min.…”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations